Effects of historic and projected climate change on the range and impacts of an emerging wildlife disease. (9th May 2019) - Price, Stephen J.; Leung, William T. M.; Owen, Christopher J.; Puschendorf, Robert; Sergeant, Chris; Cunningham, Andrew A.; Balloux, Francois; Garner, Trenton W. J.; Nichols, Richard A.
Abstract: The global trend of increasing environmental temperatures is often predicted to result in more severe disease epidemics. However, unambiguous evidence that temperature is a driver of epidemics is largely lacking, because it is demanding to demonstrate its role among the complex interactions between hosts, pathogens, and their shared environment. Here, we apply a three‐pronged approach to understand the effects of temperature on ranavirus epidemics in UK common frogs, combining in vitro, in vivo, and field studies. Each approach suggests that higher temperatures drive increasing severity of epidemics. In wild populations, ranavirosis incidents were more frequent and more severe at higher temperatures, and their frequency increased through a period of historic warming in the 1990s. Laboratory experiments using cell culture and whole animal models showed that higher temperature increased ranavirus propagation, disease incidence, and mortality rate. These results, combined with climate projections, predict severe ranavirosis outbreaks will occur over wider areas and an extended season, possibly affecting larval recruitment. Since ranaviruses affect a variety of ectothermic hosts (amphibians, reptiles, and fish), wider ecological damage could occur. Our three complementary lines of evidence present a clear case for direct environmental modulation of these epidemics and suggest management options to protect species from disease. Abstract : Increasing environmental temperatures have resulted in more frequent and more severe outbreaks of ranavirus disease in UK frogs. Future climate change could threaten larval recruitment and lead to greater impacts but the results of this study point to possible mitigation steps.